Effects of rice husk mulch dosage on the growth and yield of corn - Syafrizal, Yusril; Sevirasari, Nindy; Adileksana, Cahyo; Plena, Stella Nostra Gracia (Jurnal Ilmu Pertanian, 2024)
Drought significantly affects corn phenology and yield. Rice husk mulching is a technical cultural strategy to mitigate water stress caused by drought. This research aimed to determine the optimal dosage of rice husk mulch for the growth and yield of corn. Determining the optimal dosage of rice husk mulch is essential for agricultural efficiency, environmental sustainability, and plant health. A single-factor Randomized Complete Block Design was arranged for this research. The treatment consisted of varying dosages of rice husk mulch, namely 2; 4; 6; 8 kg.m⁻² rice husk mulch and without rice husk mulch. The data were analyzed using Analysis of Variance and followed by the Post Hoc Tukey’s HSD at α= 5%. The highest of plant height (185.99 cm), number of leaves (12.58), stem diameter (23.32 mm), stem dry weight (146.40 g), leaf dry weight (37.20 g), root dry weight (53.90 g), total dry weight (237.50 g), and suppressed weeds up to 234.47% were achieved in 6 kg.m⁻² rice husk mulch. At this dosage, it impacts the optimal cob weight with cornhusk and the dry weight of the kernels. The optimal dosage of rice husk mulch was 5.9 kg.m⁻². This study shows that optimizing plant height and cob weight with cornhusk per plant are key indicators for achieving high corn yield. The study demonstrates that rice husk mulch can suppress weeds, and enhance corn growth and yield during drought, compared to conditions without rice husk mulch.